Predictive Methods and AI-Driven Solutions for Organizational Risk Management - Dorji, Tsheten (Journal of Global Economy, Business and Finance, 2025)
This paper explores the integration of predictive methods and artificial intelligence AI into risk management practices within financial organizations. It highlights how AI driven solutions, such as machine learning and natural language processing, can transform traditional risk management by enhancing the prediction and mitigation of risks. The study focuses on the applications of AI in managing financial, operational, fraud, and market risks, offering insights into implementation strategies and the challenges associated with adopting AI technologies for proactive risk management.